2012
DOI: 10.1073/pnas.1214996109
|View full text |Cite
|
Sign up to set email alerts
|

Epitranscriptional orchestration of genetic reprogramming is an emergent property of stress-regulated cardiac microRNAs

Abstract: Cardiac stress responses are driven by an evolutionarily conserved gene expression program comprising dozens of microRNAs and hundreds of mRNAs. Functionalities of different individual microRNAs are being studied, but the overall purpose of interactions between stress-regulated microRNAs and mRNAs and potentially distinct roles for microRNA-mediated epigenetic and conventional transcriptional genetic reprogramming of the stressed heart are unknown. Here we used deep sequencing to interrogate microRNA and mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 51 publications
5
74
1
Order By: Relevance
“…Significantly, a deep sequencing profile of miR expression in mouse heart [124] found that miR 133b is expressed at about 1/6 of the level of miR 133a, reflecting that microarraybased studies may underestimate the relative levels of important miR isomers. Importantly, such deep sequencing analyses also question the canonical view that miR133b is not expressed in cardiac tissue, reinforcing the need to employ sensitive and accurate analysis to extend our understanding of miR involvement in biological processes.…”
Section: Cancer and Downregulated Myomirsmentioning
confidence: 99%
“…Significantly, a deep sequencing profile of miR expression in mouse heart [124] found that miR 133b is expressed at about 1/6 of the level of miR 133a, reflecting that microarraybased studies may underestimate the relative levels of important miR isomers. Importantly, such deep sequencing analyses also question the canonical view that miR133b is not expressed in cardiac tissue, reinforcing the need to employ sensitive and accurate analysis to extend our understanding of miR involvement in biological processes.…”
Section: Cancer and Downregulated Myomirsmentioning
confidence: 99%
“…miR-22 is the most abundantly expressed miRNA in the heart. 55 Despite its high expression, this miRNA is dispensable for cardiac development and morphogenesis because the miR-22 knockout mice do not reveal any cardiac abnormalities under basal conditions. However, upon cardiac stress (isoproterenol or TAC), miR-22 knockout mice quickly develop dilated cardiomyopathy accompanied with increased deposition of fibrotic tissue.…”
Section: Nonfibroblast Mirnas Involved In Cardiac Fibrosismentioning
confidence: 99%
“…18 Furthermore, RNA sequencing is inherently quantitative, whereas "spike-in" protocols, such as the one used by Melman et al 6 to normalize quantitative Sequence data are expressed as reads per million aligned microRNA reads. GSE numbers are NCBI Gene Expression Omnibus subseries files for the original sequence data from references 7,8,10 . CM indicates cardiomyopathy; and isch, ischemic.…”
Section: Dorn Mir-30d As a Biomarker For Resynchronization Success 2173mentioning
confidence: 99%
“…Sequence data are expressed as reads per million aligned microRNA reads. GSE numbers are NCBI Gene Expression Omnibus subseries files for the original sequence data from references 7,8,10 . TAC indicates traverse aortic coarctation.…”
Section: Disclosuresmentioning
confidence: 99%